Tetrahedral DNAzymes for enhanced intracellular gene-silencing activity. Issue 68 (30th July 2018) - Thai, Hien Bao Dieu; Levi-Acobas, Fabienne; Yum, Soo-Young; Jang, Goo; Hollenstein, Marcel; Ahn, Dae-Ro
Abstract : We prepared tetrahedral DNAzymes (TDzs) to overcome potential limitations such as insufficient serum stability and poor cellular uptake of single-stranded DNAzymes (ssDzs). Abstract : We prepared tetrahedral DNAzymes (TDzs) to overcome potential limitations such as insufficient serum stability and poor cellular uptake of single-stranded DNAzymes (ssDzs). TDzs showed enhanced serum stability and higher cellular uptake efficiency compared to those of ssDzs, providing significantly improved intracellular gene-silencing activity to down-regulate the target mRNA level.